Recalcitrant Dissecting Cellulitis of the Scalp Treated Successfully with Adalimumab with Hair Regrowth: A Case Report - Alsantali A; Almalki B; Alharbi A (Dove Medical Press, 2021)
Adel Alsantali,1 Basel Almalki,2 Abdullah Alharbi3 1Department of Dermatology, Hair Disorder Unit, King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia; 2Department of Dermatology, King Abdulaziz Medical City, Ministry of National Guard, Jeddah, Saudi Arabia; 3Department of Pathology, King Fahad Armed Forces Hospital, Jeddah, Saudi ArabiaCorrespondence: Adel AlsantaliDepartment of Dermatology, Hair Disorder Unit, King Fahad Armed Forces Hospital, P.O. Box 53893, Jeddah, 21593, Saudi ArabiaEmail santli26@hotmail.comAbstract: Dissecting cellulitis (DC) of the scalp or perifolliculitis capitis abscedens et suffodiens is a rare chronic inflammatory condition of the scalp manifested by perifollicular pustules, nodules, abscesses and sinuses that result into scarring alopecia. Treatment of DC is challenging and often disappointing. We report a 38-year-old male patient with DC for 5 years, and multiple topical and systemic therapies had shown poor effect. This patient achieved excellent response to adalimumab with hair regrowth.Keywords: dissecting cellulitis, perifolliculitis capitis abscedens et suffodiens, adalimumab, TNF-α inhibitor